Optimal transfer policies - Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper discusses the role of transfers in a non-cooperative environment. If reselling in-kind-transfers involves some retrading costs, in-kind transfers are supposed to realise at least some of the mutual bargaining gains which would be left unexploited by mere use of monetary payments. These retrading costs bias the recipient's consumption plans in favour of the donor. However, the paper shows that non-enforceability alone does not support the exclusive application of inkind transfers in general because income effects can leave some scope for monetary transfers. The results of the model are discussed for some applications.
Keywords: D62; H40; 330; In-kind transfers; monetary transfers; optimal policies; Öffentlicher Transfer; Wohlfahrtstheorie; Öffentliches Gut; Theorie